2D Cs2PbI2Cl2 Nanosheets for Holistic Passivation of Inorganic CsPbI2Br Perovskite Solar Cells for Improved Efficiency and Stability. Issue 46 (27th October 2020) - Yang, Shaomin; Liu, Weiduan; Han, Yu; Liu, Zhike; Zhao, Wenjing; Duan, Chenyang; Che, Yuhang; Gu, Haoshuang; Li, Yuebin; Liu, Shengzhong (Frank)
Abstract: Inorganic CsPbI2 Br perovskite solar cells (PSCs) have gained enormous research interest due to their excellent thermal and light stabilities. However, their unsatisfactory power‐conversion efficiency and poor intrinsic phase stability remain roadblocks to their further development. Herein, Cs2 PbI2 Cl2 nanosheets (NSs) with the Ruddlesden–Popper (RP) structure are synthesized, and an NSs/CsPbI2 Br/NSs heterostructure is employed to enhance both the stability and efficiency of CsPbI2 Br solar cells. The novel Cs2 PbI2 Cl2 NSs can not only passivate the top and bottom surfaces of the perovskite film and top surface of the TiO2 film but also enhance the stability of the perovskite film. Based on the heterostructured NSs/CsPbI2 Br/NSs inorganic perovskite film, the efficiency of the CsPbI2 Br PSCs is improved from 15.02% to 16.65%. Moreover, the unencapsulated CsPbI2 Br devices with the NSs/CsPbI2 Br/NSs heterostructure sustain over 90% of their original efficiencies after being exposed to ambient conditions (≈25 °C and ≈35% RH) for 648 h. Both the UV‐light‐soaking stability (100 mW cm −1 365 nm UV light) and thermal stability ( T  = 85 °C) of the optimized devices are dramatically improved in comparison with their counterparts with only a 3D active layer. Therefore, this work promotes the application of RP inorganic perovskite nanocrystals in a range of perovskite optoelectronic devices. Abstract : Herein, novel Ruddlesden–Popper Cs2 PbI2 Cl2 nanosheets are synthesized and creatively employed as a multifunctional interface optimization material to improve the performance of CsPbI2 Br solar cells. Based on the heterostructured NSs/CsPbI2 Br/NSs inorganic film, an efficiency of 16.65% is obtained, which is one of the best reported for CsPbI2 Br solar cells, along with much‐enhanced UV, air, and thermal stabilities.